Composição da comunidade fitoplanctônica do Rio Guamá e Baía do Guajará, município de Belém (Pará, Brasil) - LIMA JUNIOR, Paulo Roberto Carvalho de (2019)
This study present had as objective to characterize the phytoplankton community Guajará bay and river Guama, since these water bodies concentrate in its margin right the port sector and have served as domestic and industrial effluents receivers. Biological samples were collected in five georeferenced stations, including two along the Guama River and three in the Bay of Guajará, monthly, during the period from June/2012 to May/2013, in horizontal hauls in subsurface water for five minutes, using conical-cylindrical plankton net (20μm mesh opening). Concomitantly, they were recorded in situ physicochemical parameters (Temperature, pH and Dissolved Oxygen) on the surface of water, within the normal for the Amazon region. A total of 36 species were identified, distributed in 25 genera, 18 families and four classes. About composition and distribution of phytoplankton community, diatoms and chlorophytes were the most representative groups. The species Aulacoseira granulata, Polymyxus coronalis and Coscinodiscus sp. were classified as little abundant and other organism considered rare. About frequency of occurrence: Polymyxus coronalis, Coscinodiscus sp., Eudorina elegans, coscinodiscus oculus-iridis and Cyclotella meneghiniana were observed with 100% frequency during the sampling period. The density was superior during the dry seasons, due to increased photic zone and consequent increase in Phytoplankton density. The diversity indices and evenness showed no significant differences between sample points. Low diversity was explained by the dominance of a few species, but in abundance. In general, the floristic composition, frequency of occurrence, density, evenness and diversity of the Guamá River and Guajará Bay are according to other estuarine aquatic ecosystems of the Amazon region.